A Monte Carlo Analysis of Actual Maximum Exposure From a 5G Millimeter-Wave Base Station Antenna for EMF Compliance Assessments - Xu, Bo; Anguiano Sanjurjo, David; Colombi, Davide; Törnevik, Christer (Frontiers in Public Health, 2022)
International radio frequency (RF) electromagnetic field (EMF) exposure assessment standards and regulatory bodies have developed methods and specified requirements to assess the actual maximum RF EMF exposure from radio base stations enabling massive multiple-input multiple-output (MIMO) and beamforming. Such techniques are based on the applications of power reduction factors, which lead to more realistic, albeit conservative, exposure assessments. In this paper, the actual maximum electromagnetic field exposure and the corresponding power reduction factors are computed for a millimeter-wave radio base station array antenna. The computed incident power densities based on near-field and far-field approaches are derived using a Monte Carlo analysis. The results show that the actual maximum exposure is well below the theoretical maximum, and the power reduction factors similar to those applicable for massive MIMO radio base stations operating below 6 GHz are also applicable for millimeter-wave frequencies. Despite the very low power levels that currently characterize millimeter-wave radio base stations, using the far-field approach can also guarantee the conservativeness of the power reduction factors used to assess the actual maximum exposure in close proximity of the antenna.